2013
DOI: 10.1590/s0100-06832013000600009
|View full text |Cite
|
Sign up to set email alerts
|

Physical quality of an Oxisol after different periods of management systems

Abstract: SUMMARYManagement systems may lead to a loss of soil physical quality as a result of removal of the plant cover and excessive agricultural mechanization. The hypothesis of this study was that the soil aggregate stability, bulk density, macro-and microporosity, and the S index and saturated hydraulic conductivity may be used as indicators of the soil physical quality. The aim was to study the effects of different periods and managements on the physical attributes of a medium-textured Red Oxisol under soybean an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
4
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 33 publications
3
4
0
2
Order By: Relevance
“…This result was also found by Rossetti, Centurion and Sousa Neto (2013). Anghinoni, Carvalho and Costa (2013) found that the tools currently used to evaluate soil physical quality are insufficient for soils under agricultural processes.…”
Section: S-index Ofsupporting
confidence: 58%
See 1 more Smart Citation
“…This result was also found by Rossetti, Centurion and Sousa Neto (2013). Anghinoni, Carvalho and Costa (2013) found that the tools currently used to evaluate soil physical quality are insufficient for soils under agricultural processes.…”
Section: S-index Ofsupporting
confidence: 58%
“…According to Rossetti, Centurion and Sousa Neto (2013), the S-index should not be recommended as a singly indicator of soil physical quality. This was also reported by Lier (2014), who explains that the estimate of soil quality based on S-index is questionable.…”
Section: Introductionmentioning
confidence: 99%
“…The same authors also observed that the degree of soil mixing in the practice of the preparation modifies the manner of distribution of the organic material, where the CT becomes this relatively uniform distribution in the arable layer (0.0-0.2 m). Rossetti et al (2013) studying the organic matter content in different tillage systems have also observed that the higher content of OM lie in surface layers and that in the CT system, there is a decrease in these levels over time due to the action of microbial decomposition, combined with increasing aeration, soil temperature, fractionation and mixing of plant residues to the soil caused by this management system. In the NT system, the P content in the layer 0.0-0.1 m were higher at other systems in the year 2009 (5.40 mg dm ).…”
Section: Ph Organic Matter and Macronutrients In Soilmentioning
confidence: 96%
“…According to Machado et al (2008), the water retention curve could directly affect the management and practices that should be used in agricultural systems. From the SWRC it is possible to determine the S index, developed by Dexter (2004aDexter ( , 2004bDexter ( , 2004c, that has been utilized as an indicator of the soils physical quality (Rosseti et al, 2013;Lima et al, 2014;Melo Filho et al, 2015). This indicator is based on the inflection point of the SWRC model proposed by van Genuchten (1980), having its values highly correlated with soil density, total porosity, macroporosity, and soil organic matter (Dexter, 2004a;Andrade & Stone, 2008;Silva et al, 2012;Cunha et al, 2011).…”
Section: Agriculturalmentioning
confidence: 99%